Single nucleotide polymorphisms of the inflamatory cytokine genes: interleukin-1B, tumor necrosis factors-A and tumor necrosis factor-B in adult patients with immune thrombocytopenia - Pavkovic M; Angelkovic R; Popova-Simjanovska M; Karanfilski O; Trpkovska-Terzieva S; Sotirova T; Cevreska L; Stojanovic A (Македонска академија на науките и уметностите. Одделение за медицински науки = Macedonian Academy of Sciences and Arts. Section of Medical Sciences/SCIENDO, 2015)
Immune thrombocytopenia (ITP) is an autoimmune disease characterized by thrombocytopenia due to platelet autoantibodies, causing an accelerated clearance of opsonized platelets by phagocytes. The etiology of ITP remains unclear, both genetic and environmental factors may have a role in the disease development. The aim of our study was to investigate a possible association of three single nucleotide polymorphisms (SNP) in the genes for interleukin beta (IL1B-511C/T), tumor necrosis factor beta (TNF+252G/A) and tumor necrosis factor alpha (TNFA-308G/A) with ITP. We have analyzed 125 adult patients with ITP and 120 healthy matched controls. Genotyping was performed by using PCR- RFLP methods. Our results demonstrated significantly different genotype distributions and allele frequencies for TNFB+252G/A in patients with ITP, p = 0.005 and p = 0.009 with Yates correction. We did not find any significant differences in the genotype distribution or allele frequencies for the other two genes. We have found significantly different genotype distribution and allele frequencies for TNFA-308G/A between patients with unresponsive and responsive ITP patients, p = 0.016 and p = 0.009. There were no significant differences in genotype distribution and allele frequencies for ILB-511C/T and TNFB+252G/A polymorphisms between those two groups of patients. We did not find any significant differences in genotype distribution and allele frequencies for all three polymorphisms between splenectomized and unsplenectomized ITP patients. The obtained data indicate that the A allele of TNFB+252G/A is more frequent in these patients than in the controls and that this polymorphism may play a significant role in disease susceptibility. The A allele of TNFA-308G/A was more frequent in patients with unresponsive ITP, indicating that this gene polymorphisms may contribute to therapy resistance.